Developmental progression and planning of training for swimmers aged 12-18 years - Richards, R. (Swimming in Australia, 2005)
There are numerous accounts of how young children progress from novice to elite swimmer. Three challenges face coaches in achieving maximum long-term performance through the age-group years and into senior swimming: (1) maintain the performance progression of early maturing athletes, (2) plan appropriate training for the majority of athletes maturing within the `normal` age-range of adolescence, and (3) nurture the late maturing individuals by keeping them in the sport and maintaining their developmental progression. All models for sporting development should embrace the principles of human growth and development and respond to individual needs. It`s also important for the coach to understand what aspects of sporting development are most sensitive to change during certain stages of physical growth and maturation. In addition, skill development and psychological maturity may still be developing (even at age 18) to a standard required by the elite senior athlete.